Literacy Achievement Levels Among Egyptian Primary School Efl Learners In An International School - Shaheen, Rania Kamal (2013)
The main aim of the present study was to investigate the extent to which Egyptian primary school learners of English as a foreign language (EFL) at an international school in Alexandria, Egypt, can succeed in acquiring literacy in English. First, the level of literacy achievement was determined. Second, it was compared to that of same-age native speakers of English at state schools in the U.K. The instrument chosen to do this was the package of tests developed by the Qualifications and Curriculum Authority of the U.K. Department of Education. The reason this package of tests was chosen is that not only does it offer a means of testing the children's level of achievement in literacy but that it also offers a means of comparing such a level to the national average in the U.K. The theoretical framework guiding this study was derived from work on the role of phoneme-grapheme correspondence rules (Lonzon, 2007), phonological awareness (Whitehurst and Lonigan, 1998), meaning (Ehri, 1992) and knowledge of oral language (Palinscar and Duke, 2004). Research by Verhoeven and Vermeer (2006) and Gundersen (2007) provided the theoretical framework for the acquisition of literacy in a language other than the learner's primary language. The sample of the study comprised 18 Arabic-speaking Egyptian children between the ages of 7 and 8 from upper-income families in the city of Alexandria that have been in the same class ever since they started school. The children's level in reading, writing and spelling was tested in May 2011 as part of their normal school exams at the end of year two.